Implementasi Model Kemp Dalam Penggunaan Quiz Wordwell Untuk Meningkatkan Keaktifan Siswa Dalam Pembelajaran PAI - Jasiah J; Muhamad Galih Riskiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this research is to increase students' activeness in learning Indonesian through the utilization of Wordwall media and the application of the Kemp model. The method used in this research is literature study, in which researchers rely on various reference sources to collect data. This research relies on books, dictionaries, journals, magazines, and other sources without the need to make direct observations in the field. Based on the results of research conducted by the author through literature review, there is a solution to the problems raised, namely the application of the Kemp model in the use of Quiz Wordwall media to increase student activeness in learning Islamic Religious Education (PAI). Kemp's model, as a flexible learning design, is very relevant to be used together with Quiz Wordwall, because it can increase student participation. The use of this technology makes learning more interesting, interactive, and in accordance with the learning characteristics of today's students. In addition, it makes it easier for teachers to design an effective, efficient, and quality learning process.